House of sand and fog - Perelman, Vadim; London, Michael (DreamWorks Home Entertainment, 2004)
Academy award winners Ben Kingsley and Jennifer Connelly deliver stunning performances as two strangers whose conflicting pursuits of the American Dream lead to fight for their hopes at any cost. What begins as a struggle over a rundown bungalow spirals into a clash that propels everyone involved towards a shocking resolution."A surprise ending that will leave you breathless!".